Apropriação do cinismo e alienação no discurso da responsabilidade social: um estudo da recepção dos beneficiários de projetos sociais de empresas - Belizário, Fernanda Branco (2008)
It aims to understand how the reception of social responsibility discourse is realized in social projects sponsored by private companies. We know this discourse can be interpreted from 2 point of views, the functionalist, which institutionalizes the official discourse, and the strategic, which understands the company’s social activism as market strategy and intention to empower its social control. So, instead of analyze only what companies say about their social projects, we tried to identify what the benefited of these project have to say about them. After the discourse analysis of them, two main reflections are possible. The first one, characterizes and presents the implications of understanding these projects as gifts by the benefiters. The second one, presents the reflection before, inside a citizenship concept, which understands the public arena as a place which creates social actors with capability of exercising rights. This capability, in the communication’s point of view, defines such as private companies’ representations in public arena, as indicates paths to circulation of different models of value institutionalization in societies